The Role of Gastronomy in Cultural Politics: Lesson Learned from Italy - Elindawati, Rifki; Nugrahani, Henny Saptatia Drajati (UI Scholars Hub, 2023)
Cultural politics is one of the efforts used by national governments in promoting culture in various countries to achieve their national interests. Italy tries to implement its cultural politics by seeing gastronomy as a diplomatic tool or gastrodiplomacy. This study attempts to seek answer for two research question, first is how does Italy intensively carry out a gastrodiplomacy as its cultural politics. The theory used in this research is the integral state of Gramsci's Hegemony. The research method that will be used in this paper is a descriptive qualitative research method analysis. Meanwhile, the data collection method used is document study data collection by gathering relevant information and data. The data source used is a secondary data source. The results of this study found that cultural policies are implemented by various elements of the state, the factors involved are non-governmental organizations, the media, educational institutions and business people to gain cultural hegemony.